Renal Function Recovery Strategies Following Marathon in Amateur Runners - Hernando, Carlos; Hernando, Carla; Panizo, Nayara; Collado-Boira, Eladio; Folch-Ayora, Ana; Martínez-Navarro, Ignacio; Hernando, Barbara (Frontiers in Physiology, 2022)
Long distance races have a physiological impact on runners. Up to now, studies analysing these physiological repercussions have been mainly focused on muscle and cardiac damage, as well as on its recovery. Therefore, a limited number of studies have been done to explore acute kidney failure and recovery after performing extreme exercises. Here we monitored renal function in 76 marathon finishers (14 females) from the day before participating in a marathon until 192h after crossing the finish line. Renal function was evaluated by measuring serum creatinine (sCr) and the Glomerular Filtration Rate (GFR). We randomly grouped our cohort into three intervention groups to compare three different strategies for marathon recovery: total rest (REST), continuous running at their ventilatory threshold 1 (VT1) intensity (RUN), and elliptical workout at their VT1 intensity (ELLIPTICAL). Interventions in the RUN and ELLIPTICAL groups were performed at 48h, 96h and 144h after marathon running. Seven blood samples (at the day before the marathon, at the finish line, and at 24h, 48h, 96h, 144h and 192h post-marathon) and three urine samples (at the day before the marathon, at the finish line, and at 48h post-marathon) were collected per participant. Both heart rate monitors and triaxial accelerometers were used to control the intensity effort during both the marathon race and the recovery period. Contrary to our expectations, the use of elliptical machines for marathon recovery delays renal function recovery. Specifically, the ELLIPTICAL group showed a significantly lower ∆GFR compared to both the RUN group (p=4.5 x 10-4) and the REST group (p=0.003). Hence, we encourage runners to carry out an active recovery based on light-intensity continuous running from 48 h after finishing the marathon. In addition, full resting seems to be a better strategy than performing elliptical workouts.